Aristobulus' interpretation of LXX sabbath texts as an interpretative key to John 5:1-18 : Septuagint conference papers (SASSSA 2006) - Swart, G. (Journal for semitics, 2009)
The aim of the present study is to examine some alternative parallels - notably the fragments of the second century B.C.E. Hellenistic Jewish philosopher Aristobulus, preserved in Book XIII.12 of the Praeparatio Evangelica by Eusebius of Caesarea - to see whether these may in any way inform the interpretation of John 5:18. The Aristobulus fragments have in fact been cited as parallels to John 5:17.18 by a few scholars; however, no study I was able to access includes a detailed discussion of what these parallel texts specifically contribute to our understanding of the argument in John 5 or of the underlying assumptions.